A re-investigation: Effect of TIG welding parameters on microstructure, mechanical, corrosion properties of welded joints. (2021) - Chaudhary, Vikash; Bharti, Ajaya; Azam, Syed Mohd; Kumar, Naveen; Saxena, Kuldeep K.
Highlights: TIG Welding is the most common joining technique for metals. Reinforcement like SiC, TiC, Gr, and CNT increases the strength of welded joints. Current and voltage should be selected carefully so that sputtering is minimum. Welding speed, voltage, and current affect the properties of TIG welded joints. Abstract: Welding and riveting are the two fundamental joining processes for metals. Welding joints have high strength than the riveting joints. But there is a high heat-affected zone in welding. The heat-affected zone is the reason for the stress concentration and pre-mature failure. The heat-affected zone and other properties (i.e., microstructural, mechanical, and corrosion) of a welded joint depends on the welding parameters. In the present work, a re-analysis of the effect of welding parameters is done on the microstructural, mechanical, and corrosion properties of the inert tungsten gas welded materials. It was observed that the grain coarsening occurred in the heat-affected zone, while in the fusion zone, grain refinement took place. Hence, the coarsening of grains reduced the hardness and tensile strength of the material in the heat-affected zone. Heat affected zone can be reduced by reducing the current, but the reduction of current reduces the penetration.